1999
DOI: 10.1111/j.1600-0684.1999.tb00279.x
|View full text |Cite|
|
Sign up to set email alerts
|

Detection of simian immunodeficiency virus (SIV)‐specific T‐cell‐mediated cytotoxicity in the peripheral blood from infected cynomolgus monkeys

Abstract: We have previously demonstrated that peptide immunization restimulates the memory CD4 T-cell response, but fails to induce cytotoxic T lymphocyte (CTL) in cynomolgus macaques. To examine the nature of protective immunity to simian immunodeficiency virus (SIV) in this study, freshly isolated peripheral blood mononuclear cells (PBMC) from four infected juvenile cynomolgus macaques and from three uninfected control macaques were assessed for CTL activity monthly for 9 consecutive months, beginning 1 month after d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2001
2001

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…The high NK cell lytic activity observed in the rhesus monkey PBMCs may be due in part to CD56 + NK cells and in part to cells expressing a phenotype different from CD56 or to cells belonging to the T-lymphocyte lineage [42]. Furthermore, we have previously shown that NK activity could be decreased by lysis of effector cells with anti-CD56 in SIV cyn -infected cynomolgus monkeys [29]. The NK cell activity shown by PBMCs was different for cynomolgus monkeys and rhesus monkeys compared with mandrills and vervets.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The high NK cell lytic activity observed in the rhesus monkey PBMCs may be due in part to CD56 + NK cells and in part to cells expressing a phenotype different from CD56 or to cells belonging to the T-lymphocyte lineage [42]. Furthermore, we have previously shown that NK activity could be decreased by lysis of effector cells with anti-CD56 in SIV cyn -infected cynomolgus monkeys [29]. The NK cell activity shown by PBMCs was different for cynomolgus monkeys and rhesus monkeys compared with mandrills and vervets.…”
Section: Discussionmentioning
confidence: 97%
“…NK cells represent an important first line of defense against viral infections, against neoplastic cell growth, and in the control of hematopoiesis [1,13,46]. Previous studies have examined the NK cell activity in some primate species (e.g., rhesus monkeys [Macaca mulatta] and cynomolgus monkeys [Macaca fascicularis]), and the cells responsible for the observed cytotoxicity activity have been, in some instances, characterized [6,27,29,55]. It was reported that the onset of human AIDS correlates with an impairment of NK cell functions [7,45].…”
Section: Introductionmentioning
confidence: 99%